Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea) - Risaro, Jessica; Williams, Gary C.; Pereyra, Daniela; Lauretta, Daniel (European Journal of Taxonomy, 2020)
Sea pens (Cnidaria: Anthozoa: Pennatulacea) constitute a distinctive group of colonial marine invertebrates. They inhabit the world`s oceans, from shallow to deep waters. Studies about this group in Argentina are scarce, and no species have been described in the area in over a decade. Based on samples collected in Mar del Plata Submarine Canyon at about 3000 m deep we describe a new species of sea pen, Umbellula pomona Risaro, Williams & Lauretta sp. nov. This is a spiculate Umbellula that differs from other species of Umbellula with sclerites, by the number, development and distribution of the autozooids in its terminal cluster, as well as the shape of its axis. Molecular data also distinguishes it from other known species. Of the forty-three described species approximately ten are considered valid for the genus Umbellula, four of them are registered for the South Atlantic Ocean and only three are described for the Antarctic region. Since sampling efforts in this area have been scarce, the number of species of sea pens from the region is likely to increase substantially in the coming years.